IMPROVING THE STUDENTS’ VOCABULARY BY USING “GO FISH” GAME - Nurman, Moh. (Journal of English Language Teaching, 2018)
The present study aims at explaining how to improve the students’ vocabulary mastery by using “Go Fish” game. The study belongs to classroom action research. The participants of the study are one hundred and twenty-two junior high school students of the seventh grade. To measure the improvement of students’ vocabulary mastery, the study used test. The finding showed that the mean score, 92,41 in the second Cycle had met the criteria of success. It means that the use of Go Fish game in teaching vocabulary can improve the students’ vocabulary mastery.